THE EXPERIENCE OF PUBLIC ADMINISTRATION OF DEVELOPMENT OF THE INFORMATION SOCIETY AND ELECTRONIC GOVERNANCE OF THE EU COUNTRIES - Serenok A.O. (Pressing Problems of Public Administration, 2016)
In the article have been analyzed the European legislations on a development of the Information Society and the experience of public administration on a development of the Information Society of the EU countries.